Risky sexual behavior among people living with HIV/AIDS in Andabet district, Ethiopia: Using a model of unsafe sexual behavior - Worede, Jejaw Berihun; Mekonnen, Alemayehu Gonie; Aynalem, Seblewongiel; Amare, Nakachew Sewnet (Frontiers in Public Health, 2022)
Introduction Human immunodeficiency virus (HIV) infection continues to be a major public health problem in Ethiopia. Previous studies have described risky sexual behavior and associated factors among HIV–positive people. These studies, however, did not use a model of unsafe sexual behavior that could address both subjective and objective factors of sexual activity, and there is no study that examines the distal aspects of risky sexual behavior among people living with HIV/AIDS in Ethiopia. Therefore, this study aimed to examine the risky sexual behavior among people living with HIV/AIDS using a model of unsafe sexual behavior. Methods An institutional-based study was conducted from March to April 2022. The sample size was determined by using Sloven's formula. In this study, both quantitative and qualitative methods were employed. Study participants were selected using systematic sampling method. An interviewer-administered questionnaire was used to collect the data. Descriptive statistics and correlation tests were computed to analyze the data. The qualitative data was analyzed thematically. Results This study included a total of 181 PLWHA clients. The average score for participants' perception regarding the facts of HIV/AIDS was 48.7% (95% CI: 38.9, 58.4). Three months prior to the study, 46.3% of study participants had engaged in at least one risky sexual activity (95% CI: 33.8, 65.4). The correlation model revealed a positive correlation between living in a rural area and risky sexual behavior (p-value = 0.001). Furthermore, a poor perception of HIV risks was associated with risky sexual behavior (p-value = 0.003). Economic issues, stigma and discrimination, and usage of substances were also identified as contributing factors to unsafe sexual activity in the qualitative data. Conclusions A high proportion of PLWHA clients had engaged in at least one risky sexual activity in the 3 months prior to the study. It is not enough to be on ART; additional educational interventions that shape the sexual behavior of PLWHA clients must be considered.